Analisis Pasar Wisata Syariah di Kota Yogyakarta - Ade Ela Pratiwi (Media Wisata, 2016)
This article is the result of research that talks about how the development of the tourism market of sharia in Yogyakarta City. Sharia travel is a new travel trend worldwide that has excellent prospects for development and this concept into new ways to develop tourism in Yogyakarta to uphold the culture and values of Islam. This study seeks to segment the tourism market in the Yogyakarta City and tourist developments seen from indicators sharia destination product and service quality, as well as formulated attributes that are required in the development of sharia travel and recommend the development of a marketing strategy of sharia in the Yogyakarta City. The descriptive method was used to describe the facts about the sharia travel market in Yogyakarta City. The results show that tourists visiting Yogyakarta come from various parts of the archipelago, with demographic and psychographic diversity. Yogyakarta has a great potential to be developed as a tourist destination with Islamic views of destination product and service quality by adding the necessary attributes and by conducting massive marketing with the promotional mix.